The relationship between organizational identification and turnover intention among operational level employees at resort X - Lee, Li Jie, 1997-, author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2019)
Project Paper (Sarjana Muda Sains (Pembangunan Sumber Manusia)) - Universiti Teknologi Malaysia, 2019